A proposal for an alternative spatial weight matrix under consideration of the distribution of economic activity - Jens K. Perret (University of Wuppertal, Schumpeter School of Business and Economics, 2011)
In economic geography all indicators and studies are based in one way or another on a measure of distances between two points of interest. The present study discusses the problems that arise in the course of calculating distances between regions. It is shown that measures presently in use are usually biased. A new measuring concept is therefore presented that takes into account the regional economic or demographic structures and constructs distances between regions accordingly.
urn:nbn:de:hbz:468-20110121-161923-4
Keywords: R11; R15; 330; Russian Federation; Spillovers; Spatial Economectrics; Spatial Weights; Regionale Entwicklung; Spillover-Effekt; Regionalökonomik; Russland